Valéria e Henrique: o entrelaçar da constituição de suas subjetividades - Isabela Costa Dominici (2021)
The present work was developed from questions about the process of constituting the subjectivity of babies and seeks to dialogue with the existing literature on the subject in order to explore what has been produced and thought about. Such dialogue focuses on works that allow theoretical deepening, especially with Historical-Cultural Psychology and Ethnography in Education. In order to make a contrastive analysis, which is one of the proposals of our theoretical-methodological orientation, we chose two babies as expressive cases according to the following criteria: (I) need to break with the paradigms that do not consider the development of babies by gender , ethnic-racial, socioeconomic and family aspects; (II) consider the different uses of language by babies, whether spoken, written, drawing, gestures, facial expressions, looks, crying, hugging, affection and, finally (III) the production of speech / language in use from the relationships of these babies with other babies, teachers and researchers focusing on the following questions: with whom? Where? When? Because? Under what conditions? What we defend and what was produced by us during the development of this work is that in order to understand the constitution of the subjectivity of Valéria and Henrique it was necessary to perceive them in their entirety. We understand that “the holistic understanding of this totality is a step towards understanding that the human being is not the sum of its parts, but their meeting in a dialectical unit, which presupposes [situated social affection / cognition / cultures / languages in use] - (ACCL)” constituting a social being that is individualized in this meeting. Therefore, we defend in this thesis that the process of constituting the subjectivities of Valéria, Henrique and the babies is social, singular and situated in the cultural contexts of their production. Being a younger sister, having teachers in her family, devising strategies to have adult attention, being communicative, expressing interest in eating times, experiencing literacy events at school and at home and being interested in written, gestural and spoken communication are hallmarks of the process of constituting Valéria's subjectivity. Being an only child, being encouraged to help with house work, having stories with his parents, playing games, having food preferences, having a cultural practice for the moment of sleep are marks of the constitution of Henrique's subjectivity. Such marks that differentiate them were found in the collective space of EMEI TUPI and intertwined, enabling Valéria and Henrique, as well as other babies to recognize themselves as different people from each other and enhance what affected them, bringing them closer and further apart in the collective individualization process.